Quantifiable design and comparative evaluation of straight-line minimally invasive endodontic cavity based on the anatomical features of the coronal part of root canal - Ziteng Long; Ruijun Song; Chenyi Zhao; Yixuan Miao; Xutao Luo; Xingbo Wu; Dingming Huang; Lan Zhang (Journal of Dental Sciences, 2023)
Background/purpose: Minimally invasive endodontics has recently become popular in research. This study aimed to develop a new quantifiable straight-line minimally invasive endodontic cavity (SMIEC) for 3-rooted maxillary first molar based on the anatomical features of the coronal part of root canal. Materials and methods: Cone-beam computed tomography (CBCT) images of 80 teeth were converted into models in Mimics Research software. Anatomical features of the coronal part of root canal were measured to develop SMIECs with straight-line accesses to root canals in 3-matic Research software. Twenty models were randomly sampled and each was duplicated for 8 simulation groups: non-treated (NT), traditional endodontic cavity (TEC), ninja endodontic cavity (NEC) and 5 SMIECs. Post-simulation models were subjected to finite element analysis to detect von-Mises stresses in ABAQUS software. Results: Distributions of straight-line accesses to protogenetic root canals had certain manners, hence we developed 5 SMIECs. NEC and SMIECs had less hard tissue loss than TEC and presented different numerical rankings in different structures (P < 0.05). NEC had a less narrow surgery field than SMIECs except SMIEC2/4 (P < 0.05). The peak pericervical stresses of SMIECs were similar, lower than TEC and higher than NEC and NT (P < 0.05). The stress distributions of the 8 groups had certain manners. Conclusion: Five SMIECs with straight-line accesses to root canals were developed, whose biomechanical properties were worse than NEC but better than TEC. Having appropriate structure preservation and surgery field, SMIEC2/4 was a preferred SMIEC.